Exploitation of nanoparticle-protein interactions for early disease detection - Papi, Massimiliano; Palmieri, Valentina; Palchetti, Sara; Pozzi, Daniela; Digiacomo, Luca; Guadagno, Elia; del Basso De Caro, Marialaura; Di Domenico, Marina; Ricci, Serena; Pani, Roberto; Mahmoudi, Morteza; Di Carlo, Angelina; et al. (Applied physics letters, 2019)
The main diagnostic tools for primary and metastatic central nervous system (CNS) tumors are the anamnestic neurological examination and the imaging tests, which are expensive and lack specificity. In recent years, the shell of macromolecules which forms on nanoparticles (NPs) when they are exposed to human blood, also known as hard corona (HC), became a powerful tool in diagnostics. Indeed, HC can act as a “nano-concentrator” of serum proteins and can detect minor changes in the protein concentration at the very early stages of disease development. In this paper, we characterized lipid NP HC formed in blood samples from patients affected by meningeal tumors. We found that the HCs of meningeal tumor patients could be discriminated from those of healthy subjects. Our results show that emerging HC-based technologies will pave the way for early diagnosis of CNS cancer.